study of association between visual disturbances and neural findings in patients with cerebral venous sinus thrombosis - نتوف أروى; سعيد هالة; رجب محمود (Latakia University Journal -Medical Sciences Series, 2022)
Background: Symptoms of cerebral venous sinus thrombosis are highly variable and varied, which is difficult to diagnose and treat early. In this prospective study, we will shed light on the visual symptoms and their association with neurological findings. The goal of the study: It is the assessment of ophthalmic symptoms and signs in patients with cerebral venous sinus thrombosis and their relationship to prognosis. Methods:The study included 72 patients, from the Division of Neurological Diseases at Tishreen University Hospital in Lattakia, who were diagnosed with cerebral venous sinus thrombosis, during one year (from January 5, 2021 to January 5, 2021). Results and discussion: The sample of the study included 72 patients suffering from cerebral venous sinus thrombosis, the incidence of females is greater than males, the percentage of females was 68.1%, due to hormonal reasons related to pregnancy, puerperium, menopause and hormonal drugs. A predisposing cause of cerebral venous sinus thrombosis can be detected in approximately 70% of patients, the most important of which is infections, 23.6%, followed by the use of oral contraceptives, 19.7%. Headache and blurred vision were the most important symptoms that patients sought medical advice for. Visual disturbances were found in patients with cerebral venous sinus thrombosis by 72.2%, and the most frequent is papilledema, which was reported in nearly 80% of patients. More than half of the patients had thrombosis in more than one venous sinus. the Most common sinus thrombosis is the superior sagittal sinus and transverse sinuses. The prognosis of cerebral venous sinus thrombosis was good in the case of early diagnosis and treatment, as more than half of the patients were cured, and ocular sequelae were recorded nearly five times more than the neurological sequelae, where the bad prognosis of cerebral venous sinus thrombosis was associated with - Presence of one of the following eye disorders: papilledema, visual field defects, severe visual impairment, diplopia, and orbital pain. - multiple sinuses affected by thrombosis -High cerebrospinal fluid pressure - Oldest age. Conclusion: Cerebral venous sinus thrombosis manifests with a wide range of heterogeneous and non-specific symptoms. The investigation of visual disturbances and understanding the mechanisms of their pathological occurrence plays an important role in guiding the diagnosis and early treatment of cerebral venous sinus thrombosis and avoiding neurological and ophthalmological sequelae. It also plays a pivotal role in determining the prognosis.